2019
DOI: 10.32854/agrop.vi0.1488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de trampas para Rhynchophorus palmarum L. (Coleoptera: Curculionidae) en la costa de Oaxaca, México

Abstract: Objetivo: Evaluar la efectividad de las trampas CSAT modificada y PET en la captura del picudo negro del cocotero Rhynchophorus palmarum L. (Coleóptera: Curculionidae) en Río Grande, Tututepec, Oaxaca, México.Diseño/metodología/aproximación: Para capturar R. palmarum en una huerta de cocotero Enano Malayo Amarillo cv. Acapulco, durante 2016-2018 se instalaron trampas CSAT modificada y PET, ambas con Rincoforol como feromona y plátano Tabasco como cebo alimenticio. Con el registro de captura de cada siete días,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The semiochemical is the primary control tool for this pest, participating in several mass-trapping opportunities with fresh and fermenting food lures. Much of the researchers’ concern has focused on the pure trapping ability of the devices [ 67 , 68 ], but studies on the cost/efficacy of attractant combinations [ 69 , 70 ] and the use of traps in ornamental palm polycultures [ 71 , 72 , 73 , 74 , 75 ] exist. Technology today suggests the usage of digital tools also to study the efficacy of traps [ 76 ].…”
Section: The Genus Rhynchophorus Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…The semiochemical is the primary control tool for this pest, participating in several mass-trapping opportunities with fresh and fermenting food lures. Much of the researchers’ concern has focused on the pure trapping ability of the devices [ 67 , 68 ], but studies on the cost/efficacy of attractant combinations [ 69 , 70 ] and the use of traps in ornamental palm polycultures [ 71 , 72 , 73 , 74 , 75 ] exist. Technology today suggests the usage of digital tools also to study the efficacy of traps [ 76 ].…”
Section: The Genus Rhynchophorus Sppmentioning
confidence: 99%
“…The aggregation pheromone alone is not as effective as needed in capturing adult R. palmarum , even if released at around 30 mg/day into the environment. Evidence suggests that the synergy among the plant kairomones, the pheromone, rotting plant parts such as sugar cane stalks, and ethyl acetate significantly captured more insects [ 70 , 73 , 91 ].…”
Section: Rhynchophorus Spp Pheromone and Other Attractive Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, there is the possibility that at the end of autumn the temperature is lower and with this it is preferable for the flight and population fluctuation of R. palmarum, compared to spring and summer, where temperatures are higher. In this sense, Ovando-Cruz et al (2019) reported an increase in the capture of R. palmarum in the month of December (3.67 adults/trap/week), when temperatures could be lower compared to the months of July (1.80 adults/trap/week) and august (2.03 adults/trap/week), where temperatures could be higher. It is clear that more studies are required to clarify these scenarios, if we want to know the behavior of R. palmarum and use this information for its integrated management in coconut orchards.…”
Section: Discussionmentioning
confidence: 95%
“…Population dynamics of Rhynchophorus species can be tracked over time using baited pheromone traps, which can be used to assess effects of climate, location, host palm species, trap-type efficacy, and time of year on weevil densities (2,38,131,161,180,202). Weevil density time series data derived from trap capture data can be correlated with palm mortality rates (110) and used to determine impacts of multiyear management programs (102) and to evaluate spatiotemporal factors influencing range expansion patterns following invasions into new areas (85) or infestation patterns in commercial palm plantations (49).…”
Section: Developmental Biology Rearing and Population Dynamicsmentioning
confidence: 99%